Ehe, Familie und Agamie Die Begründung von Lebensformen angesichts gesellschaftlicher Pluralität im Neuen Testament und heute - Becker, Matthias (Mohr Siebeck, 2025)
Within the pluralistic context of Greco-Roman culture, the New Testament offers a variety of reasons to justify marriage, family, and celibacy. Matthias Becker presents these justifications in detail and relates his findings to current debates on family forms in academic theology and the church.
PublicationDate: 20250313
Keywords: Antikes Christentum -- neutestamentliche Ethik -- Ehe- und Familienethik -- Ehe und Familie im Römischen Reich -- Mohr Siebeck Taschenbuch -- Neues Testament -- Antike Religionsgeschichte -- Alte Geschichte -- Ethik -- Antike Philosophie -- Handbuch